Persepolis Treasury Tablets Old and New - Cameron, G. G.
Wood Reliefs, Wood Carvers, and Metal Workers – Wine and Winemakers – Treasury Accountants, Accounting Practices, and Royal Domains. Appendix (Persepolis Treasury Texts in Teheran).